2013
DOI: 10.4161/epi.26701
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent patterns of DNA methylation in theZNF154,CASP8, andVHLpromoters across a wide spectrum of human solid epithelial tumors and cancer cell lines

Abstract: (2013) Recurrent patterns of DNA methylation in the ZNF154, CASP8, and VHL promoters across a wide spectrum of human solid epithelial tumors and cancer cell lines, Epigenetics, 8:12, 1355Epigenetics, 8:12, -1372

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 75 publications
7
61
0
Order By: Relevance
“…Using an early array-based method three groups profiled 1505 CpGs (Illumina GoldenGate) [6567] considering tumor grade and histotype in their analyses (Table 1). Several studies used normal ovarian or fallopian tissue as the control [11,12,66,6870] while the other studies used hierarchical clustering to discern the methylation patterns within EOC cases [20,65,67], making comparison between analyses difficult. However, significant histotypespecific methylation was noted both between histotypes and when compared to a normal tissue.…”
Section: Dna Methylation Analyses In Eocmentioning
confidence: 99%
“…Using an early array-based method three groups profiled 1505 CpGs (Illumina GoldenGate) [6567] considering tumor grade and histotype in their analyses (Table 1). Several studies used normal ovarian or fallopian tissue as the control [11,12,66,6870] while the other studies used hierarchical clustering to discern the methylation patterns within EOC cases [20,65,67], making comparison between analyses difficult. However, significant histotypespecific methylation was noted both between histotypes and when compared to a normal tissue.…”
Section: Dna Methylation Analyses In Eocmentioning
confidence: 99%
“…Hypermethylation of the promoter region has been recognized as the most recurrent mechanism causing functional loss of caspase 8 gene. However, although the association between aberrant DNA methylation of caspase 8 and carcinogenesis has been demonstrated in several studies (Sánchez-Vega et al, 2013;Liedtke et al, 2005), the functional relevance of this epigenetic trait in melanomagenesis has not yet been fully understood (Fulda et al, 2001). Our findings, showing for the first time that caspase 8 expression has been impaired by DNA hypermethylation following Cd treatment in all tested cutaneous melanoma cell lines (Figs.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast with these studies of DNA hypermethylation, Sánchez-Vega et al showed hypomethylation in a genomic region near the CASP8 tumour suppressor promoter in endometrioid cancer compared with normal tissue (124). This gene is located at chromosome 2q33.1 and encodes a cysteineaspartic acid protease (caspase) that plays an important role in cell apoptosis.…”
Section: Dna Methylation In Endometrial Cancermentioning
confidence: 97%
“…Methylation in this gene was correlated with higher gene expression as well as higher levels of histone marks (H3K4me3 and H3K27ac) which are associated with the promoters of actively transcribed genes. The authors suggested that CASP8 demethylation can restore gene expression and trigger cell death in cancer cells (124). The mechanism of CASP8 demethylation is unknown; possibly, it could be a consequence of global hypomethylation of the cancer genome.…”
Section: Dna Methylation In Endometrial Cancermentioning
confidence: 99%